Developing IMB-KPI Conceptual Framework for Integrating Religious Moderation into the Islamic Education Curriculum - Siti Nur Hidayatul Hasanah; Bani (MUNIF: International Journal of Religion Moderation, 2026)
This study develops the Integrating Religious Moderation Values into the Islamic Education Curriculum (IMB-KPI) Conceptual Framework as a holistic model for curriculum transformation in Islamic education. The study addresses the conceptual limitation of previous research that has predominantly positioned religious moderation as an instructional strategy, character education program, or learning outcome rather than as the philosophical foundation of curriculum development. A library research approach employing a narrative literature review design was adopted to synthesize contemporary scholarship on religious moderation, Islamic education, curriculum development, integrated curriculum, and value-based education. Documentary data were collected from books, government policy documents, and peer-reviewed publications indexed in Scopus, Web of Science, ERIC, and nationally accredited journals, followed by qualitative content analysis involving identification, coding, categorization, conceptual synthesis, and interpretation. The findings demonstrate that religious moderation should function as a cross-cutting educational value embedded throughout curriculum objectives, learning contents, instructional strategies, learning resources, assessment systems, hidden curriculum, and school culture. The resulting IMB-KPI framework integrates Islamic educational philosophy, classical curriculum theories, and integrated curriculum perspectives into a coherent conceptual model that promotes balanced religious understanding, inclusive citizenship, critical thinking, ethical leadership, and peaceful coexistence. The framework contributes theoretically by reconceptualizing religious moderation as the organizing principle of curriculum transformation while providing practical guidance for curriculum developers, educational leaders, teachers, and policymakers seeking to strengthen holistic Islamic education through sustainable curriculum reform.